Improvement of keratorefractive lenticule creation by application of a vortex beam in an ultraviolet femtosecond laser system - Hammer, Christian M.; Zhang, Yao; Klafke, Mario; Paulsen, Friedrich; Lörner, Johannes (Journal of Cataract and Refractive Surgery, 2025)
Purpose: To examine the effect of a vortex beam on gas formation and interface quality after keratorefractive lenticule creation with a 347 nm UV femtosecond laser. Setting: “masked for peer-review”. Design: Experimental study. Methods: Refractive corneal lenticules were created in 40 ex vivo porcine eyes with a 347 nm UV femtosecond laser. In 20 eyes, the laser was operated with a (Laguerre-Gaussian) vortex beam (generated by a spiral phase plate), and in the remaining 20 with a normal (Gaussian) beam. In each group, 12 eyes were used for histological quantification of intraoperative gas formation. The remaining 8 eyes were subjected to scanning electron microscopy after lenticule extraction to evaluate the lenticule bed morphology. The vortex group was compared morphologically and morphometrically to the normal group. Results: Application of a vortex beam significantly decreased the amount of gas produced intraoperatively. Semiquantitative 2D histomorphometrical analysis of the area occupied by gas bubbles yielded 20,156 ± 5,591 µm2/mm in the normal samples, as compared to 9,495 ± 3,966 µm2/mm in the vortex samples (p<0.001). Moreover, the lenticule beds created by a UV vortex beam were markedly smoother and more regular than those created by a normal UV laser beam. Conclusions: Operating a UV femtosecond laser with a vortex beam may significantly decrease the risk of opaque bubble layer formation and increases surgical safety and precision.
CRIS-Team Scopus Importer:2025-05-09
Keywords: femtosecond laser; lenticule extraction; refractive surgery; ring focus; vortex beam